EVALUATING THE EFFICIENCY OF NON-PHARMACOLOGICAL PAIN MANAGEMENT TECHNIQUES DURING LABOR AND DELIVERY - KAKAR, PK; ANILA, MF; KHAN, AGM; SINDHU, S (Biological and Clinical Sciences Research Journal, 2023)
Labor and delivery is a natural procedure that causes women significant pain and discomfort. Many women choose pharmacological pain management techniques, yet there is growing interest in non-pharmacological pain management techniques, viewed as safer and more natural than pharmacological methods. This study aimed to assess the efficacy of non-pharmacological pain management techniques during labor and delivery. In a randomized controlled trial, we randomly assigned 246 expectant women to either a non-pharmacological intervention or a control group. During labor and delivery, the non-pharmacological intervention group received a combination of relaxation techniques, including massaging and physical therapy, aromatherapy, TENS, and mixed interventions. The control group received standard care devoid of non-pharmaceutical interventions. Pain levels were measured using a visual analog scale at 30-minute intervals. Additionally, the length of labor, delivery mode, and birth outcomes were recorded using the APGAR score system. The demographic characteristics of patients in both groups were comparable and non-significant in variations (p>0.05). Forty participants utilized each non-pharmacologic technique. Comparing VAS pain scale scores at 30-minute intervals, the distribution of pain intensity levels was comparable between the groups. The larger fraction of neonates in the non-pharmacological group had higher APGAR scores, indicating no need for immediate medical attention. Based on a reasonable comparison of the effectiveness of various interventions for managing labor pain and distress, it was found that 9 (22.5%) of 40 patients who received massaging therapy reported low efficacy in managing labor pain, 13 (32.5%) reported moderate efficacy, and 28 (70%) reported high efficacy. In the aromatherapy of 40 patients, 16 reported low efficacy, 21 reported moderate efficacy, and 13 reported high efficacy in managing labor pain. Ten patients (25%) reported low efficacy, 12 patients (30%) reported moderate efficacy, and 28 patients (70%) reported high efficacy in managing labor pain through TENS. It provided cost-effective and safe alternatives to pharmaceutical interventions during labor and delivery. When properly implemented, these techniques reduced pain intensity comparable to commercial medicines while significantly improving the birthing experience and potentially contributing to better maternal and neonatal outcomes.